Safety measures in entrepreneurs - thota, Monisha (Journal of Management and Science, 2020)
An entrepreneur is a person who seeks to benefit from any given opportunity, rather than working all day long as an employee, with a fixed routine. He or she works according to a plan of their own. Entrepreneurs are a very important donator in any economy. These are the people who have the initiative and skills necessary to anticipate recent and future needs and bring great new ideas to market. But with every positive aspect there comes some negative aspects too, which should not be overlooked. So we need to understand every highs and lows of being an entrepreneur.